Answer
![\left( \begin{array}{l l}x=-3+ 3√(3), & y=-3+2√(3)\\\\x=-3- 3√(3), & y=-3-2√(3)\end{array}\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/b7bgk7did4hg26lqhls56u66dqid0oh2qh.png)
Explanation:
Given system of equations:
![\begin{cases}x-2y+(x)/(y)=6\\\\x^2-2xy-6y=0 \end{cases}](https://img.qammunity.org/2023/formulas/mathematics/high-school/6zw7g5rgbrt2gh59gm2380dx2ftr12d1ph.png)
Rearrange the second equation to isolate y:
![\implies x^2-2xy-6y=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/z2k7pj67zbgy2jn10x6eyzzvjug30q3tan.png)
![\implies x^2=2xy+6y](https://img.qammunity.org/2023/formulas/mathematics/high-school/plx33q6vexpe6xhpeozaoeyvtynx3y71a6.png)
![\implies x^2=y(2x+6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/zm87f6xorzb9gmt674mb0czw5784504p8k.png)
![\implies y=(x^2)/(2x+6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vzf8nv5t91s4luyfgo3bokhilplhbxm6ka.png)
Substitute the found expression for y into the first equation:
![\implies x-2\left((x^2)/(2x+6)\right)+(x)/((x^2)/(2x+6))=6](https://img.qammunity.org/2023/formulas/mathematics/high-school/cn1q1tkh0kdpi6xaigk6s5yd2zgk4evyto.png)
![\implies x-(x^2)/(x+3)\right)+(2x+6)/(x)-6=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/duw5l7kk7ot2zjbz89fnpwx2i877iiz3xa.png)
![\implies (x^2(x+3))/(x(x+3))-(x^3)/(x(x+3))\right)+((2x+6)(x+3))/(x(x+3))-(6x(x+3))/(x(x+3))=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/gabrhodllkonmp1uz2udt2uia8cam7ulq5.png)
![\implies (x^2(x+3)-x^3+(2x+6)(x+3)-6x(x+3))/(x(x+3))=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/c3qlrac59g52bhbj3y7g6zjzf7vw6qztv8.png)
![\implies x^3+3x^2-x^3+2x^2+12x+18-6x^2-18x=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/43jkcvxj4yc5mpo5kvk6twwxisq5pvtggy.png)
![\implies -x^2-6x+18=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/96lwa79z860imijvmhs53uqvenp4pbi7wp.png)
Solve using the Quadratic Formula.
Quadratic Formula
![x=(-b \pm √(b^2-4ac) )/(2a)\quad\textsf{when }\:ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/physics/high-school/srcbg1ukkzuvprrhg8mwvjtfb23umv2fbh.png)
Therefore:
![\implies x=(-(-6) \pm √((-6)^2-4(-1)(18)) )/(2(-1))](https://img.qammunity.org/2023/formulas/mathematics/high-school/jojfa0k8jfinm5bdeak1ny35js5noasz6l.png)
![\implies x=(6 \pm √(108))/(-2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/qu6gclm0o1k61xu394aqa7red6qfqpp78c.png)
![\implies x=(6 \pm √(36 \cdot 3))/(-2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/67si0vsb5opslkni5qn1elreftl8f9adx6.png)
![\implies x=(6 \pm √(36)√(3))/(-2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/lkmxgiqywbnolaf4857v6qpwyhm8qxugrl.png)
![\implies x=(6 \pm 6√(3))/(-2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/g0bqa5to6zfxbfcahxgjv49arbyl0plt0x.png)
![\implies x=-3\pm 3√(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/261bisds1lurrnbolamqkcggrkewls37d1.png)
Substitute the found values of x into the expression for y:
![\textsf{When }x=-3+3√(3):](https://img.qammunity.org/2023/formulas/mathematics/high-school/knsjq3pyxlcmb9hi26w3g9llfklemiwn15.png)
![\implies y=((-3+3√(3))^2)/(2(-3+ 3√(3))+6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/5iukdcey02sw5tllwtmy0zalls0ldhpqx7.png)
![\implies y=(36-18√(3))/(6√(3))](https://img.qammunity.org/2023/formulas/mathematics/high-school/dngmy7zyn9ex702ozl9nyezi19hyhg8v6g.png)
![\implies y=(36)/(6√(3)) -(18√(3))/(6√(3))](https://img.qammunity.org/2023/formulas/mathematics/high-school/t9879vgwcl1dhlqwe47tcfhk2pk5vn8sx7.png)
![\implies y=(6√(3))/(√(3)√(3)) -3](https://img.qammunity.org/2023/formulas/mathematics/high-school/l0yhfvyps10e607co7iqyuqbkmhjn5p3l8.png)
![\implies y=-3+2√(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/eyf987i95pptl3z7nvdkdjerh0qqm3d94o.png)
![\textsf{When }x=-3-3√(3):](https://img.qammunity.org/2023/formulas/mathematics/high-school/wd71m5jxyd2gl25radp7iaygwinz61se3r.png)
![\implies y=((-3- 3√(3))^2)/(2(-3- 3√(3))+6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vbylucofjcugmiw7j4nwuin304zqk9m6d9.png)
![\implies y=(36+18√(3))/(-6√(3))](https://img.qammunity.org/2023/formulas/mathematics/high-school/on22p9l4zh1n24q0y9urqricswpi1iq2h5.png)
![\implies y=(36)/(-6√(3))+(18√(3))/(-6√(3))](https://img.qammunity.org/2023/formulas/mathematics/high-school/xz3p8m7qjy8c3ozyc9xlw8elr3az220v7w.png)
![\implies y=-(6)/(√(3))-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/vhwif7nmihfiommw9bgsjclv5vfnhp1dhw.png)
![\implies y=-(6√(3))/(√(3)√(3))-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/qunb25r7nwdplgrcrpu1bevrzbuclta1aa.png)
![\implies y=-3-2√(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/o3p9acm6rq2iruu7s3aaidvmkishvim68s.png)
Therefore, the solutions are:
![\left( \begin{array}{l l}x=-3+ 3√(3), & y=-3+2√(3)\\\\x=-3- 3√(3), & y=-3-2√(3)\end{array}\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/b7bgk7did4hg26lqhls56u66dqid0oh2qh.png)